Psychosocial Assessment of Candidates for Transplant (PACT) as a tool for psychological and social evaluation of allogeneic hematopoietic cell transplantation recipients - Hong, Sanghee (Bone Marrow Transplant, 2019)
Psychosocial Assessment of Candidates for Transplant (PACT) is a tool originally developed to address psychosocial risks in solid organ transplant recipients and has the potential for application to hematopoietic cell transplantation (HCT) recipients. In a retrospective cohort study, we reviewed 404 adult allogeneic HCT cases from 2003 to 2014 to identify predictors of adverse psychosocial status as determined by PACT. Final PACT rating was poor/borderline (score 0–1) in 5%, acceptable (score 2) in 22%, good (score 3) in 44%, and excellent (score 4) in 29% recipients. In multivariable regression, higher PACT score was associated with White race (odds ratio [OR] 2.95, P < 0.001), having a related donor (OR 1.61, P = 0.015), and a higher quality of life score (OR 1.22/ 10-point increase in FACT-BMT total score, P < 0.001). PACT score correlated with all quality of life subscales. The final PACT score was associated with non-relapse mortality (HR 0.82/ 1-point increase, p = 0.03) in multivariable analysis that considered patient and disease factors, but not in models that also included transplant-related factors and performance status. PACT score was not associated with overall survival. PACT can be considered as part of a comprehensive psychosocial assessment for identifying patients who may require additional resources around allogeneic HCT.